COVID-19 Pandemic and Global Inequality Reflections in Labour Market, Business and Social Sectors - Bhattacharyya, Rajib; Das, Ramesh Chandra; Ray, Achintya (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
The book intends to capture the most critical issue that has cropped up as an aftermath of the Corona pandemic- the phenomenon of widening of global inequalities across nations depending upon their economic position, support policies of the government and international relationship particularly in the context of alarming growth of unemployed in the labour market, business activity and social sector. This book is expected to provide new areas of research to both academicians and policy makers to re-think about global cooperation for bridging the inequalities for a better world. It tries to incorporate the valuable contribution of experts from various fields of knowledge in a consolidated volume. This text will be revised once the chapters are finalized and put together in structured themes. The table of content lists some of the chapters that have been confirmed, but there are more that are being invited by the editors.
The impact of Covid-19 on sustainable development in Europe: a temporal analysis -- Global Liquidity under Covid-19: Unconventional Monetary Policies and Rising Inequalities -- Digital Movement and Implications on Sustainable Development in Post Pandemic Time: An Introspection with Special Reference to India -- Impact of Foreign Trade and COVID-19 Pandemic on Sri Lankan and Indian Economy: A Comparative Study -- Determining the right strategies for Turkey to avoid an energy crisis during the pandemic process -- The Impact of COVID-19 Pandemic on the Incidence of Poverty, Economic Growth and Development: Evidence from Ghana -- COVID-19 and Impact on Income Inequality: The Indian Experience -- COVID-19 Pandemic, Employment Differential and Health Expenditure nexus in sub-Saharan African Countries: Evidence from vector Autoregressive (VAR) model -- Covid -19 and the Informal Sector of India's Economy: An Econometric Analysis -- COVID-19 Pandemic, Health Crisis and Financial Stability -- Impact of COVID-19 Pandemic on Basic education in South Asian Countries: An Exploratory Analysis -- Covid 19, Online Education & Role of Mentoring in Developing Economies- A Theoretical Build-up with an empirical Overhaul -- COVID-19 Pandemic and its impact on Access to Safe Drinking Water: A Case Study.
Keywords: Labor economics; Welfare economics; Welfare state; Social policy; Labor Economics; Social Economy; Welfare; Social Policy